2001
DOI: 10.1074/jbc.m009430200
|View full text |Cite
|
Sign up to set email alerts
|

Scp160p, an RNA-binding, Polysome-associated Protein, Localizes to the Endoplasmic Reticulum of Saccharomyces cerevisiae in a Microtubule-dependent Manner

Abstract: Scp160p is an RNA-binding protein containing 14 tandemly repeated heterogenous nuclear ribonucleoprotein K-homology domains, which are implicated in RNA binding. Scp160p interacts with free and membranebound polysomes that are dependent upon the presence of mRNA. Despite its presence on cytosolic polysomes, Scp160p is predominantly localized to the endoplasmic reticulum (ER). Accumulation of Scp160p-ribosome complexes at the ER requires the function of microtubules but is independent of the actin cytoskeleton.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 50 publications
10
116
0
Order By: Relevance
“…The latter distributions were as expected, since most ribosomes are present in cytoplasm while Scp160 is enriched with ribosomes at the ER (Supplemental Fig. S9A; Frey et al 2001). Together, the cellular distributions of Scp160, Sec61, Pgk1, and Rpl35 proteins demonstrate that the fractionation into membrane and cytoplasmic fractions was successful.…”
Section: Sesa Inhibits Translation Of Pom34 Mrnasupporting
confidence: 79%
See 2 more Smart Citations
“…The latter distributions were as expected, since most ribosomes are present in cytoplasm while Scp160 is enriched with ribosomes at the ER (Supplemental Fig. S9A; Frey et al 2001). Together, the cellular distributions of Scp160, Sec61, Pgk1, and Rpl35 proteins demonstrate that the fractionation into membrane and cytoplasmic fractions was successful.…”
Section: Sesa Inhibits Translation Of Pom34 Mrnasupporting
confidence: 79%
“…We therefore tested whether the interaction of the mRNA-binding protein Scp160 with Smy2 and Eap1 could restrict translation inhibition to a specific subset of mRNAs, which may bind to SESA through the known mRNA-binding protein Scp160 (Frey et al 2001). Attempts to identify mRNAs that were clearly regulated by Scp160 on the level of translation were unsuccessful.…”
Section: Eap1 Allows Bypass Of Mps2 Function By Inhibiting Translatiomentioning
confidence: 99%
See 1 more Smart Citation
“…2d). Functionally, this contact site appears important because RACK1 interacts with the polysomeassociated protein Scp160, which promotes mRNA binding 15,16 . RACK1 is involved in the PKC (protein kinase C) dependent phosphorylation of initiation factor 4E, which promotes polysome-dependent de novo protein synthesis 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we reported that the eIF4E-binding protein Eap1p functions as a translation initiation inhibitor in cells treated with CPZ and in mutants that block secretory or endocytic pathways (e.g., sec4 and end3). Interestingly, Eap1p was shown to interact genetically and biochemically with Scp160p (Mendelsohn et al 2003), a ribosomal protein localized to the endoplasmic reticulum (Frey et al 2001). It will be thus interesting to determine if Eap1p is essentially dedicated to the control of the expression of genes whose products are transported along the secretory pathway.…”
Section: Figmentioning
confidence: 99%